A Scanning Electron Microscope Study on the Effect of an Experimental Irrigation Solution on Smear Layer Removal - Zand, Vahid; Mokhtari, Hadi; Lotfi, Mehrdad; Rahimi, Saeed; Sohrabi, Aydin; Badamchi Zadeh, Sina; Mojaver Kahnamooie, Hanieh; Tehranchi, Pardis (Iranian Endodontic Journal, 2014)
Introduction: The aim of this in vitro study was to evaluate the effect of an experimental irrigation solution, containing two different concentrations of papain, Tween 80, 2% chlorhexidine and EDTA, on removal of the smear layer. Methods and Materials: Thirty-six single-rooted teeth were divided into two experimental groups (n=12) and two positive and negative control groups of six. The canals were prepared with BioRaCe instruments up to BR7 (60/0.02). In group 1, canals were irrigated with a combination of 1% papain, 17% EDTA, Tween 80 and 2% CHX; in group 2, canals were irrigated with a combination of 0.1% papain, 17% EDTA, Tween 80 and 2% CHX. In group 3 (the negative control), the canal was irrigated with 2.5% NaOCl during instrumentation and at the end of preparation with 1 mL of 17% EDTA was used; in group 4 (positive control), normal saline was used for irrigation. The amount of the remaining smear layer was quantified according to Hulsmann method using scanning electron microscopy (SEM). Data was analyzed by the Kruskal-Wallis and Mann-Whitney tests. Results: Two-by-two comparisons of the groups revealed no significant differences in terms of smear layer removal at different canal sections between the negative control group (standard regiment for smear layer removal) and 1% papain groups (P<0.05). Conclusion: Under the limitations of the present study, combination of 1% papain, EDTA, 2% chlorhexidine and Tween 80 can effectively remove smear layer from canal walls.